A militância de lésbicas feministas e a visibilidade nas políticas públicas para mulheres - Piason, Aline da Silva (2014)
This thesis presents studies that aimed at offering visibility to the political and social struggles of lesbian-feminist women in the context of Public Policies for Women. Objective: research, considering studies of social psychology and feminist gender studies, as national policy plans for women are enables visualization and including the demands of lesbians; and investigate how articulate themselves women who self-identify as lesbians and feminists, activists of the Brazilian League of Lesbians of Rio Grande do Sul, in actions of social movement in search of inserting their claims and acquisition of rights in public policies women, while Brazilian citizens. Method: in the composition of the thesis, four studies were conducted. The first study aimed to present reflections on issues related to women's studies and the place of lesbian women and their claims, presents in the history of feminism. The second study presents an analysis of documents on the I and II PNPM, aiming to investigate if the discourses present in the shaft of health, sexual and reproductive rights policies are enables visualization the specific demands of lesbians. The third study concerns three reflections on PNPM, aiming to investigate and understand the construction of discourses present in the axis of coping against racism, sexism and lesbophobia are enables visualization the specific demands of lesbians. In studies of documentary analysis of PNPM, Atlas / Ti computer tool was used, which has been an important feature of qualitative research methodology. Finally, the fourth study presents the research conducted by the method of participant observation, which aimed to understand how women who self-identify as lesbian and who actively participate in the LBL-RS are articulating, to achieve visibility and to ensure rights in the sphere of the National Secretariat of Policies for Women. Results: Was possible to identify, from the analyzes of PNPM, which over its three editions, have occurred important changes that promoted the visibility of lesbians demands, though still recognized as insufficient and incipient to the wide range of needs and political actions specificities. It was also recognized that acquired visibility in the political and social scenario, happened because of the important role of the actresses of the social movement of the Brazilian League of Rio Grande do Sul, in claiming their rights for the construction of public policies for all women. Conclusion: However, it was possible to see how psychology has to grow at the time they propose to dialogue with social movements and give voice to the silenced and invisibilized people in our society, and to recognize in social psychology, the insertion of the analysis field of construction of public policies that promote the right to life and citizenship. Keywords: Feminisms, Gender, Lesbian, Public Policy, Social Movements.